2021
DOI: 10.2147/mder.s300726
|View full text |Cite
|
Sign up to set email alerts
|

Thermographic Assessment of Reperfusion Profile Following Using a Tourniquet in Total Knee Arthroplasty: A Prospective Observational Study

Abstract: Background: Infrared thermal imaging is a non-invasive technique capable of detecting changes in temperature that could ultimately signify changes in blood supply. Flir One is a smartphone-based thermal camera, working by a downloadable application, capable of detecting the limb temperature through a non-contact method using infrared thermography technology. Using the Flir One camera, we will assess the lower limb reperfusion profile following the tourniquet release post total knee arthroplasty (TKA). Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Applying a tourniquet during the TKA procedure modifies the blood flow and therefore may affect knee ST. Alisi et al 33 reported that ST of the ankle region decreased on application of a tourniquet during a TKA procedure. However, ST levels returned to pre-procedural levels 20 min after tourniquet release.…”
Section: Discussionmentioning
confidence: 99%
“…Applying a tourniquet during the TKA procedure modifies the blood flow and therefore may affect knee ST. Alisi et al 33 reported that ST of the ankle region decreased on application of a tourniquet during a TKA procedure. However, ST levels returned to pre-procedural levels 20 min after tourniquet release.…”
Section: Discussionmentioning
confidence: 99%